Mathematical Modelling and Optimization of an Industrial Activity Using a Queuing Model - Andrei-Robert CIULEI; Bianca-Maria CÂRNU; Elena-Corina CIPU (Communications of International Proceedings, 2021)
The paper presents the waiting model M (m, 1, s) among the main models used in Waiting Theory. Based on the mathematical model used, the behaviour of some equipment with low failure rates is analysed in order to improve the dynamic process on the economic flow of a company. Based on the results of the models, the final conclusions are exemplified.
Keywords: Queuing Theory; Operational Research; Applied Mathematics.